Small mammal insectivore stable carbon isotope compositions as habitat proxies in a South African savanna ecosystem. (August 2016) - Leichliter, Jennifer N.; Sponheimer, Matt; Avenant, Nico L.; Sandberg, Paul A.; Paine, Oliver C.C.; Codron, Daryl; Codron, Jacqueline; Passey, Benjamin H.
Abstract: Carbon isotope analysis of fossil micromammalian insectivores holds promise for resolving questions about past environments because these animals have restricted home ranges and are generalist feeders. Thus, their diets likely integrate ecological information about local habitats. In this study, we assessed the degree to which carbon isotope compositions of three sympatric shrew species record spatial changes in habitat in a mosaic southern African savanna environment. Sampling sites were located within 2 km of one another, and microhabitat conditions ranged from very open (<5% canopy cover) to wooded ( 60% canopy cover). We compared shrew hair δ 13 C values between microhabitat types, and across taxa, in order to test whether these data follow predictable patterns based on local vegetation. Shrew carbon isotope compositions varied with habitat in a predictable manner within our study area. While taxonomy also influenced δ 13 C values, this was largely due to differences in habitat preferences of individual taxa and the resultant variation in their relative abundance within each environment. Isotopic differences between habitat types were preserved within taxa where taxa occurred in multiple habitats. To complement this modern study, we performed isotopic analysis of the enamel of insect-eating fossil micromammals from the hominin sites Gladysvale and Sterkfontein in the Cradle of Humankind, South Africa. This subset of fossil micromammals consumed primarily C4 -derived carbon. Highlights: Stable carbon isotope analysis of insectivorous small mammals is proposed as a method for inferring ancient habitats. Carbon isotope compositions of small mammalian insectivores in a modern savanna reflect habitat types. Preliminary data suggest fossil insectivores from Sterkfontein and Gladysvale consumed primarily C4 -derived carbon.